Detection of delamination between steel bars and concrete using embedded piezoelectric actuators/sensors - Zhu, X.; Hao, Hong; Fan, K. (Springer, 2013)
The interface between concrete and steel in reinforced concrete governs the interaction between thetwo types of materials under loading. When the interface is seriously damaged, such that a macro-crack is formed, debonding may take place or large slip may occur, and the load-transferring capacity of the interface would drop dramatically. This paper presents a novel technique to detect the delamination between the steel bars and concrete in the reinforced concrete structures. The piezoelectriccomponents are mounted on reinforcing bars embedded in RC structures as sensors and actuators to generate the signal, which is sensitive to the delamination between the steel bars and concrete. The experimental study is carried out on two concrete slabs with different debonds between the rebars and concrete. Three parameters are calculated from the measured responses and used to indicate thebonding damage. The test results show that the debond damage between the rebars and concrete can be detected with the embedded piezoelectric sensors and actuators.